Requirements for the German Retail Horticulture from an Economic Perspective. A Qualitative Approach in the Context of Service Controlling (Global Journal of Science Frontier Research, 2017)
The present paper is the first part of a study on value creation with regard to customer integration in retail horticulture. It deals with the determination of the requirements for German retail horticulture (RHG) from a business perspective in the context of applied service controlling. To this end, seven entrepreneurs of selected RHGs were interviewed in guided interviews. Previous investigations in horticulture have ignored this topic, so the current paper performs the necessary investigation of the factors influencing operational controlling in the balancing act between final sale and horticultural services. For the evaluation, Mayring’s qualitative content analysis is used, supplemented by a quantitative intensity analysis (scaling structuring) and a contingency analysis. This approach serves to concretize the transcribed text passages to paint a clear and comprehensive picture of individual aspects of RHG controlling. The requirements for operational controlling are displayed in a detailed category framework. It turns out that the companies offer a consistently broad range of services to varying degrees. A causal link between the categories “Service Range” and “Degree of Specialization” could not be established, since specialized companies also had a broad, generalized service-spectrum, and inverted broad-based companies spun the services into separate service divisions. Whether RHG should be “more retail-oriented” or “more service-oriented” depends on operational factors (e.g., chronicle and company management) and the competitive environment that determines the individual case. A delineation of the departments is visible in some companies when using the central category “own autonomous service department (ASD)”. In addition, influencing variables were disclosed that indicate a higher level of organization of individual enterprises. The overwhelming majority of companies surveyed show a homogeneous structure within the category framework, so structured contro
Keywords: retail horticulture; horticultural services; service controlling; value added; process organization; customer involvement; customer orientation